GAMBARAN PERILAKU IBU NIFAS TENTANG PERAWATAN BAYI SEHARI-HARI DI KELURAHAN BAGAN PETE KOTA JAMBI TAHUN 2011 - Nelly Herwani (Universitas Batanghari Jambi, 2014)
More than 50% of infant deaths occur in the neonatal period is the first month of life. Inadequate infant care can cause a variety of infectious diseases through the umbilical cord, eyes and ears both at the time of bathing the baby and the day to day maintenance. To care for a newborn who needed adequate enough knowledge about newborn care, such as how to bathe the baby, taking care of the umbilical cord, eyes, ears and exclusive breastfeeding. Data from one of the existing private midwives in villages Pete Chart 3 of 5 people found puerperal women who gave birth, did not know how to care for the baby after returning home later. This is due to lack of knowledge of the mother.This is a descriptive study using a cross sectional design conducted to describe the behavior of new mothers about infant care daily in the Village Bagan Pete City of Jambi in 2011. The population in this study were all postpartum women in September of 2011, with a total sample of 48 postpartum women. Sampling technique with a total sampling conducted on 20 to 30 September 2011. Univariate analysis of the data.The results of this study showed that of the 48 respondents, 30 (60.2%) of respondents were well behaved, 18 (37.5%) are less well behaved especially peilaku mother clean the umbilical cord, 22 (45.8%) had good knowledge, 26 (54.2%) of respondents have less knowledge of good preparation, especially before breastfeeding mothers and 47 (97.7%) of respondents have a high motivation, and 10 (20.8%) of respondents have low motivation in terms of smearing the mammary areola with breast milk before feeding.From the results of these studies are expected to midwives in order to provide information about daily baby care to mothers who have completed maternity clinic before returning home.Keyword : maternal behavior, postpartum, baby care